Visible Spectrophotometric Determination of Olmesartan Medoxomil in Pharmaceutical Formulations - Sharma, T.; Moitra, S.K.; Si, S.C.; Gowrisankar, D. (Asian Journal of Chemistry, 2012)
Two simple and sensitive spectrophotometric methods (method A and method B) in the visible region have been developed for determination of olmesartan medoxomil in bulk and in pharmaceutical formulations. Method A is based on oxidative coupling of olmesartan medoxomil with 3-methylbenzothiazolin-2-one hydrazone (MBTH). The resulting green complex has lmax at 631 nm. Method B is based on the reduction of ferric to ferrous ions followed by complexation with 1,10-phenanthroline to produce an orange red chromogen at lmax 510 nm. Beers law is obeyed in the concentration range of 10-45 μg/mL and 5-35 μg/mL respectively. These methods were extended to pharmaceutical formulations and there was no interference from excepients and diluents. The proposed methods are simple, sensitive, accurate and suitable for quality control applications.